Estimates of the prevalence of motor speech disorders in children with idiopathic speech delay. (3rd August 2019) - Shriberg, Lawrence D.; Kwiatkowski, Joan; Mabie, Heather L.
ABSTRACT: The goal of this research was to obtain initial estimates of the prevalence of each of four types of motor speech disorders in children with idiopathic Speech Delay (SD) and to use findings to estimate the population-based prevalence of each disorder. Analyses were completed on audio-recorded conversational speech samples from 415 children recruited for research in idiopathic SD in six USA cities during the past three decades. The speech and motor speech status of each participant was cross-classified using standardized measures in the finalized version of the Speech Disorders Classification System described in the Supplement. Population-based prevalence estimates for the four motor speech disorders were calculated from epidemiological studies of SD conducted in Australia, England, and the USA. A total of 82.2% of the 415 participants with SD met criteria for No Motor Speech Disorder at assessment, 12% met criteria for Speech Motor Delay, 3.4% met criteria for Childhood Dysarthria, 2.4% met criteria for Childhood Apraxia of Speech, and 0% met criteria for concurrent Childhood Dysarthria and Childhood Apraxia of Speech. The estimated population-based prevalence of each of the first three motor speech disorders at 4 to 8 years of age were Speech Motor Delay: 4 children per 1, 000; Childhood Dysarthria: 1 child per 1, 000; and Childhood Apraxia of Speech: 1 child per 1, 000. The latter finding cross-validates a prior prevalence estimate for Childhood Apraxia of Speech of 1–2 children per 1, 000. Findings are interpreted to indicate a substantial prevalence of motor speech disorders in children with idiopathic SD. Abbreviations: CAS, childhood apraxia of speech; CD, childhood dysarthria; CND, complex neurodevelopmental disorders; DI, dysarthria index; DSI, dysarthria subtype indices; MSD, motor speech disorder; No MSD, no motor speech disorder; NSA, normal(ized) speech acquisition; PEPPER, programs to examine phonetic and phonologic evaluation records; PM, pause marker; PMI, pause marker index; PSD, persistent speech delay; PSE, persistent speech errors; SD, speech delay; SDCS, speech disorders classification system; SDCSS, speech disorders classification system summary; SE, speech errors; SMD, speech motor delay.